The Postmodernist Relativization of Truth: A Critique - Asghar, Jamil; Asghar, Jamil (Islamic Studies, 2012)
Postmodernism constitutes a headlong attack on modernist claims about the existence of meaning, rationality and value—claims that stem from the eighteenth century Enlightenment. In contesting past assumptions, it displays an obsession with the inadequacy of language and once again truth is the first casualty in this battle of texts and contexts. Dismissive and disputatious of all the notions of meaning and truth, postmodernism poses a challenge to all religious orientations which uphold these notions earnestly. It has replaced ontology with a scientistic and analytic epistemology which has been proved fatal for most of the notions of truth and reality as in this epistemology the individual Cartesian consciousness of the thinking subject is taken to be the source of all reality and truth. The analytic philosophy and Derrida’s deconstruction have worked hand in glove with postmodernism to undermine the notion of truth. The present paper attempts to show the problematic nature of these philosophies and their built-in incompetence to gain access to truth. The paper is an elucidation of Islamic conceptualization of truth as interpreted by the traditionalist school and which has been contrastively studied against the Western postmodern background. The author has aspired to undertake a reasoned critique of postmodern notions of truth and has presented the essential nature of truth as propounded by Islamic epistemology. The study aims at showing how humans have a profound need to believe that truth is rooted in the unchanging depths of the universe. One of the premises of the study is that truth is determined by the way things are and it is quite independent of our knowing it.